IDENTIFICATION AND CONTROL STRATEGY APPLIED IN LOAD MANAGEMENT OF RESIDENTIAL AIR-CONDITIONERS - Hussain, Syed Ameenuddin (2004)
Saudi power utilities are under increasing need for controlling the power demand because of severe limitations of power generation resources. Loads with energy storage characteristics like Air-conditioners, Space heaters, etc. are considered as best suited for Demand-side load management scheme having the objective of changing the power demand profile. In this work the steps towards Direct Load Control (DLC) which have shown promising results are addressed. These steps involve identifying the parameters of systems and applying the control strategies as forced duty cycles. An integrated simulation environment was developed wherein the identification and control algorithm were implemented. Also, foundation was laid for carrying out the implementation of this simulated environment on a real Air-Conditioner (A/C) system.